WORK MOTIVATION, DISCIPLINE, AND WORK CULTURE ON WORK SATISFACTION AND TEACHER PERFORMANCE AT STATE JUNIOR HIGH SCHOOL, SUKAJADI DISTRICT - Dewi Sukmawaty; Sudarno Sudarno; Rizaldi Putra (Institut Bisnis dan Teknologi Pelita Indonesia, 2021)
Teacher performance is the result of work in quality and quantity that is achieved by a teacher in carrying out their duties in accordance with their responsibilities, so that teacher performance can be influenced by motivation, discipline, and work culture as well as job satisfaction. This study aims to see whether there is an influence between work motivation, discipline, and work culture with job satisfaction and teacher performance at public junior high schools in Sukajadi district. The population is 95 people and a sample of 77 teachers is obtained from 4 public junior high schools in Sukajadi sub-district. Data analysis techniques include Outer Model and Inner Model as well as Bootstrapping using SmartPLS 3 software. The results show that work motivation has a positive effect on teacher job satisfaction, work motivation also has a positive effect on performance. Then, work discipline has a positive effect on job satisfaction but discipline has no positive effect on teacher performance. And work culture has a positive effect on teacher job satisfaction, it also has a positive effect on teacher performance. While job satisfaction has a positive effect on teacher performance, this can be interpreted that teacher job satisfaction can improve teacher performance.